Korelasi dan pengaruh kualiti pengajaran guru mata pelajaran Bahasa Malaysia terhadap pencapaian dan minat pelajar di tingkatan peralihan - Lim, Chai Wan (2009)
The objective of the study is to identify the relationship between quality of instruction of the Bahasa Malaysia teacher and the student's interest and achievement in Bahasa Malaysia. The respondents were chosen from a secondary school in Butterworth, Penang. The aspects studied include lesson planning, content coverage, and teacher's enthusiasm, the use of various teaching aids, assessment and feedback. The instruments used in this research were adopted from the model of Slavin, that is, 14 categories of quality instruction applied in the classroom. Questionnaires were administered to 155 Remove Classes (year 2009) students. The instrument consists of 62 items categorized into five scales. Three hypotheses were formulated and tested by using both the Pearson product moment correlation and t-test. The result showed that quality of instruction was at a less than satisfactory level. The result showed that there were significant and positive correlations between quality of instruction and the student's interest. The teacher's quality of instruction in lesson planning, content coverage, teacher's enthusiasm, assessment and feedback all showed significant and positive correlations with student's achievement in Bahasa Malaysia. However the result showed that there were no significant correlations between the use of various teaching aids and the student's achievement. The t-test did not indicate any significant difference between the quality of instruction of the Bahasa Malaysia teacher and gender. In short, the students' interest and achievement in the subject depends very much on the application of quality instruction and enthusiasm of the subject teachers